Community Service on the Improvement of Clean Environement Based on Waste Bank in the Sub-District of Bahari Belawan (PKM Peningkatan Kebersihan Lingkungan Berbasis Bank Sampah di Kelurahan Bahari Belawan) - Mhd. Pujiono; Budi Agustono; T. Kassa Rullah Adha (LOGISTA - Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The activity of community service on the improvement of area’s hygiene in the district of Bahari Belawan is one of the appropriate activities in improving the hygiene and awareness of the people on the importance of keeping their area clean. Within this community service, the team together with Yayasan Fajar Sejahtera (YAFSI) and the government officer Belawan Bahari district have conducted socialization about the importance of hygienity and ways to manage and dump the waste properly. The method utilized is lecturing method, question and answer, demonstration and simulation. The lecturing method and question and aswer used to provide knowledge and theories about a clean environment. The simulation and demonstration method were used in order to train the people to practice what they have received about the management and development of waste bank. After the socialization had been conducted, the community service team has facilitated the waste bank in Bahari Belawan district and assisting the society in managing it. The result of this community service is an increase in awareness from the public regarding the importance of disposing and managing waste and creating economic opportunities from waste through managing plastic waste into economic value items such as paving blocks.Keywords: waste bank, socialization, clean environment, Bahari Belawan distict.